Laminated organic light-emitting device and application thereof
By adopting a connection layer structure consisting of a first connection layer, an interface modification layer and a second connection layer in the stacked organic electroluminescent device, and introducing a decreasing doping concentration process into the first connection layer, the problems of high driving voltage, low luminous efficiency and short life in the existing devices are solved, and the device performance of high efficiency, low driving voltage and long life are achieved.
Patent Information
- Application Number
- CN202411801485.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-04
AI Technical Summary
The existing stacked organic electroluminescent devices have problems such as high driving voltage, low luminescence efficiency and short life.
The connecting layer structure consisting of a first connecting layer, an interface modification layer and a second connecting layer arranged in sequence from bottom to top. The first connecting layer is made of an n-type dopant material and an organic electron transport material. The doping concentration of the n-type dopant material of the interface modification layer is greater than that of the first connecting layer. The second connecting layer is composed of a p-type dopant material and an organic hole transport material. A doping concentration reduction process of the n-type dopant material is introduced into the first connecting layer.
It effectively alleviates the energy level mismatch problem between the connecting layers, reduces the driving voltage, improves the luminous efficiency and device life, and realizes a stacked organic electroluminescent device with high efficiency, low driving voltage and long life.
Smart Images

Figure CN119767944A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroluminescence, and in particular to a stacked organic electroluminescent device and its application. Background Art
[0002] Organic light-emitting diodes (OLEDs) technology is currently widely used in small and medium-sized display products such as smartphones and wearable devices. Furthermore, OLED lighting devices that combine single-color or multi-color (three primary colors or complementary two-color) luminescent materials can also be used in indoor (outdoor) lighting, automotive lighting and other fields. OLED lighting devices have put forward more stringent requirements on the light output efficiency, aging life, operating temperature and other indicators of luminescent materials, and the device structure and its preparation process often play a decisive role in the performance of luminescent materials.
[0003] OLED lighting products usually need to have high brightness, low driving voltage and long working life performance. For this reason, a connection layer (charge generation layer, CGL) structure is needed to connect multiple light-emitting units in series to obtain a stacked OLED device. Compared with a single light-emitting unit device, the luminous brightness of the stacked device under the same current drive will increase exponentially, and a longer device life will be obtained. In order to obtain high-performance stacked OLED devices, the following two technical difficulties need to be solved for the connection layer unit: 1) In order to obtain a low driving voltage, it is necessary to solve the energy level mismatch problem of the connection layer heterojunction, thereby reducing the driving voltage drop on the connection layer unit; 2) The stacked OLED device needs to achieve a doubling effect of luminous efficiency. Therefore, each light-emitting unit needs to maintain a high-performance luminous efficiency consistent with a single light-emitting unit device, which requires the connection layer to achieve efficient generation of carriers and transport them to the light-emitting unit, so that the carriers in the device light-emitting layer can efficiently recombine and emit light. Therefore, it is urgent to develop new connection layer materials and device structures with low driving voltage and excellent luminous performance.
[0004] Academic researchers and panel manufacturers have conducted relevant research on solving the technical problems of the connection layer. For example, in patent application CN114520301A, a stacked organic light-emitting device is disclosed, in which a spacer layer structure is introduced between the n-type doped layer and the p-type doped layer to prevent the n-type dopant from easily diffusing into the p-type doped layer and the adjacent light-emitting layer, thereby causing the device driving voltage to rise. On the other hand, patent application CN116583133A proposes an alternating interface modification layer structure to reduce the injection barrier of carriers into the first connection layer and the second connection layer, thereby reducing the driving voltage drop of the stacked device at the connection layer, so that the stacked organic electroluminescent device has the characteristics of low driving voltage and high efficiency. Although the above-mentioned connection layer structure scheme can solve the energy level mismatch problem of the heterojunction, its preparation process is complicated, and there is still a voltage drop at the alternating interface.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a stacked organic electroluminescent device and its application, aiming to solve the problems of high driving voltage, low luminous efficiency and short life of the existing stacked organic electroluminescent devices.
[0007] In order to solve the above technical problems, the present invention provides a stacked organic electroluminescent device in a first aspect, comprising: an anode layer, at least two light-emitting units, a cathode layer, and a connecting layer for connecting two adjacent light-emitting units arranged in sequence from bottom to top; the connecting layer comprises a first connecting layer, an interface modification layer, and a second connecting layer arranged in sequence from bottom to top;
[0008] The interface modification layer is made of an n-type dopant material and an organic electron transport material, the first connection layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the interface modification layer is greater than the doping concentration of the n-type dopant material of the first connection layer;
[0009] The second connection layer is composed of a p-type dopant material and an organic hole transport material.
[0010] As an improvement of the above solution, the doping concentration of the n-type dopant material of the first connecting layer gradually decreases from the interface modification layer side to the light-emitting unit side;
[0011] As an improvement of the above solution, the doping concentration of the n-type dopant material of the first connecting layer decreases in a linear decreasing manner from the interface modification layer side to the light emitting unit side.
[0012] As an improvement of the above solution, the doping concentration of the n-type dopant material of the first connecting layer decreases in a gradient manner from the interface modification layer side to the light-emitting unit side, and the set concentration gradient number is an integer greater than or equal to 3.
[0013] As an improvement of the above solution, the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the interface modification layer is 5 mass % to 15 mass %, and the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the light-emitting unit is 0.5 mass % to 5 mass %.
[0014] As an improvement of the above solution, the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the interface modification layer is 5 mass % to 15 mass %, and the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the light-emitting unit is 0.5 mass % to 5 mass %.
[0015] As an improvement of the above solution, the thickness of the first connecting layer is 5nm to 60nm;
[0016] The thickness of the interface modification layer is 1 nm to 10 nm;
[0017] The thickness of the second connection layer is 10 nm to 150 nm.
[0018] As an improvement of the above scheme, the n-type dopant material is selected from at least one of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, gold, silver, copper, iron, zinc, platinum, palladium, ruthenium, ytterbium, molybdenum trioxide, vanadium pentoxide, tungsten trioxide, cesium fluoride, cesium carbonate, lithium fluoride, lithium carbonate, 8-hydroxyquinolinate lithium, sodium chloride, and ferric chloride.
[0019] As an improvement of the above scheme, the organic electron transport material is made of nitrogen heterocyclic units, and the nitrogen heterocyclic units are selected from at least one of compounds N-1 to compounds N-58:
[0020]
[0021]
[0022]
[0023]
[0024] As an improvement of the above solution, the p-type dopant material of the second connecting layer is a deep LUMO energy level material, and the deep LUMO energy level material is selected from at least one of MoO3, WO3, V2O5, MoO2, Co3O4 and the following compounds HI-1 to HI-18:
[0025]
[0026]
[0027] The second aspect of the present invention further provides an application of the stacked organic electroluminescent device, wherein the stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.
[0028] The implementation of the present invention has the following beneficial effects:
[0029] The connection layer in the present invention includes a first connection layer, an interface modification layer, and a second connection layer arranged in sequence from bottom to top. The interface modification layer further introduced between the first connection layer and the second connection layer effectively alleviates the energy level mismatch problem between the two connection layers, thereby obtaining a better carrier generation capability, so that the stacked device has no voltage drop at the connection layer. The doping concentration of the n-type dopant material of the interface modification layer is greater than the doping concentration of the n-type dopant material of the first connection layer. Setting a smaller doping concentration of the n-type dopant material on the side close to the light-emitting unit can effectively avoid the problem of exciton quenching of the light-emitting unit by the n-type dopant material, thereby improving the luminous efficiency and device life of the stacked device. In summary, the present invention obtains a stacked organic electroluminescent device with high efficiency, low driving voltage, and long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 : A schematic structural diagram of a stacked organic electroluminescent device in the present invention;
[0031] Reference numerals:
[0032] 100, anode layer; 101, hole injection layer; 102, first hole transport layer; 103, second hole transport layer; 104, first light-emitting layer; 105, second electron transport layer; 106, first electron transport layer; 107, first light-emitting unit; 108, second light-emitting unit; 310, first connecting layer; 320, interface modification layer; 330, second connecting layer; 109, third hole transport layer; 110, fourth hole transport layer; 111, second light-emitting layer; 112, fourth electron transport layer; 113, third electron transport layer; 114, electron injection layer; 115, cathode layer. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail with specific embodiments below. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be understood that, under the premise of no conflict, any and all embodiments of the present invention can be combined with the technical features in any other embodiment or multiple other embodiments to obtain another embodiment. The present invention includes such a combination to obtain another embodiment.
[0035] In this specification, groups and substituents thereof can be selected by those skilled in the art to provide stable structural moieties and compounds. When substituents are described by conventional chemical formulas written from left to right, the substituents also include chemically equivalent substituents obtained when the structural formula is written from right to left.
[0036] The section headings used in this specification are only for the purpose of organizing the article and should not be interpreted as limiting the subject matter described. All documents or portions of documents cited in this invention, including but not limited to patents, patent applications, articles, books, manuals and papers, are incorporated herein by reference in their entirety.
[0037] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.
[0038] It should be understood that the singular forms used in the present invention, such as "a", include plural references unless otherwise specified. In addition, the term "comprising" is an open limitation and not a closed one, that is, it includes the contents specified in the present invention, but does not exclude other aspects.
[0039] In order to solve the above problems, the present invention provides a stacked organic electroluminescent device in the first aspect. Figure 1 , including: an anode layer 100, at least two light-emitting units, a cathode layer 115, and a connecting layer for connecting two adjacent light-emitting units, which are arranged in sequence from bottom to top; the connecting layer includes a first connecting layer 310, an interface modification layer 320, and a second connecting layer 330, which are arranged in sequence from bottom to top. The interface modification layer 320 further introduced between the first connecting layer 310 and the second connecting layer 330 effectively alleviates the energy level mismatch problem between the two connecting layers, thereby obtaining a better carrier generation capability, so that the stacked device has no voltage drop at the connecting layer.
[0040] Specifically, see Figure 1 In one embodiment, the stacked organic electroluminescent device includes two light-emitting units, namely a first light-emitting unit 107 and a second light-emitting unit 108. The first light-emitting unit 107 is arranged between the first connecting layer 310 and the anode layer 100, and the second light-emitting unit 108 is arranged between the second connecting layer 330 and the cathode layer 115, wherein the first light-emitting unit 107 includes a first light-emitting layer 104, and the second light-emitting unit 108 includes a second light-emitting layer 111.
[0041] The first connecting layer 310 is made of an n-type dopant material and an organic electron transport material, and the interface modification layer 320 is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the interface modification layer 320 is greater than the doping concentration of the n-type dopant material of the first connecting layer, so that the doping concentration of the n-type dopant material on the side close to the first light-emitting layer 104 is small, which can effectively avoid the problem of exciton quenching of the first light-emitting layer 104 by the n-type dopant material, thereby improving the luminescence efficiency and device life of the stacked device.
[0042] Furthermore, the doping concentration of the n-type dopant material of the first connecting layer 310 decreases gradually from the side of the interface modification layer 320 to the side of the first light-emitting layer 104, which helps to reduce or even eliminate the electron injection energy level barrier between the first connecting layer 310 and the interface modification layer 320, thereby making the carrier generation ability of the connecting layer stronger and reducing the voltage drop problem caused by energy level mismatch.
[0043] In some specific and preferred embodiments, the doping concentration of the n-type dopant material of the first connection layer 310 decreases from the interface modification layer 320 side to the first light-emitting layer 104 side of the first light-emitting unit 107 in a linear decreasing manner. The doping concentration of the n-type dopant material is reduced in a linear decreasing manner, which can reduce the LUMO electron injection energy level barrier between the first connection layer 310 and the interface modification layer 320, so that electrons can enter the first connection layer 310 from the interface modification layer 320 without an injection barrier. At this time, the doping concentration of the n-type dopant material on the side of the first connection layer 310 close to the interface modification layer 320 is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connection layer 310 close to the first light-emitting unit 107 is in the range of 0.5 mass % to 5 mass %.
[0044] Alternatively, the doping concentration of the n-type dopant material of the first connecting layer 310 decreases gradually from the interface modification layer 320 side to the first light-emitting layer 104 side in a gradient decreasing manner. Compared with the linear decreasing manner of the doping concentration, the gradient decreasing manner can reduce the difficulty of the preparation process. The number of concentration gradients set is an integer greater than or equal to 3, preferably 3 to 6. If the number of concentration gradients is set too much, it will increase the difficulty of the process and is not conducive to simplifying the preparation process. At this time, the doping concentration range of the n-type dopant material on the side of the first connecting layer 310 close to the interface modification layer 320 is 5 mass% to 15 mass%, and the doping concentration range of the n-type dopant material on the side of the first connecting layer 310 close to the first light-emitting unit 107 is 0.5 mass% to 5 mass%.
[0045] Preferably, the thickness of the first connection layer 310 is 5 nm to 60 nm, and the thickness of the interface modification layer 320 is 1 nm to 10 nm.
[0046] Optionally, the n-type dopant material in the first connection layer 310 and the interface modification layer 320 is selected from at least one of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, gold, silver, copper, iron, zinc, platinum, palladium, ruthenium, ytterbium, molybdenum trioxide, vanadium pentoxide, tungsten trioxide, cesium fluoride, cesium carbonate, lithium fluoride, lithium carbonate, 8-hydroxyquinolinate lithium, sodium chloride, and ferric chloride. The n-type dopant material of the first connection layer 310 and the n-type dopant material of the interface modification layer 320 can be the same substance or different substances. The organic electron transport material is composed of a nitrogen heterocyclic unit, and the nitrogen heterocyclic unit is selected from at least one of compound N-1 to compound N-58. The organic electron transport material of the first connection layer 310 and the organic electron transport material of the interface modification layer 320 can be the same substance or different substances.
[0047] Preferably, the second connecting layer 330 is made of a p-type dopant material and an organic hole transport material, the p-type dopant material of the second connecting layer 330 is a deep LUMO energy level material, the deep LUMO energy level material is selected from MoO3, WO3, V2O5, MoO2, Co3O4 and at least one of the following compounds HI-1 to HI-18, and the organic hole transport material is described in detail later.
[0048]
[0049]
[0050] Furthermore, the second connection layer 330 has a thickness of 10 nm to 150 nm.
[0051] The first light-emitting unit 107 includes a hole injection layer 101, a first hole transport layer 102, a second hole transport layer 103, a first light-emitting layer 104, a second electron transport layer 105 and a first electron transport layer 106, which are arranged in sequence from bottom to top; the second light-emitting unit 108 includes a third hole transport layer 109, a fourth hole transport layer 110, a second light-emitting layer 111, a fourth electron transport layer 112, a third electron transport layer 113 and an electron injection layer 114, which are arranged in sequence from bottom to top.
[0052] The hole injection layer 101 can promote hole injection into the first hole transport layer 102, thereby reducing the driving voltage of the organic electroluminescent device and improving the luminous brightness and device life. The thickness of the hole injection layer 101 is not particularly limited, and is preferably 1 nm to 150 nm.
[0053] Furthermore, the material of the hole injection layer 101 includes a hole injection material, and the hole injection material is preferably an organic hole transport material.
[0054] The organic hole transport material is an aromatic amine compound, and the aromatic amine compound is one or more of the following formula (I) and formula (II);
[0055]
[0056] In formula (I) and formula (II),
[0057] Ar1 to Ar4 are substituted or unsubstituted aromatic hydrocarbon groups having 6 to 50 ring carbon atoms, or fused aromatic hydrocarbon groups having 6 to 50 ring carbon atoms with a substituent, or substituted or unsubstituted aromatic heterocyclic groups having 5 to 50 ring atoms, or substituted or unsubstituted fused aromatic heterocyclic groups having 5 to 50 ring atoms, or groups formed by bonding the above aromatic hydrocarbon groups or fused aromatic hydrocarbon groups with aromatic heterocyclic groups or fused aromatic heterocyclic groups. A ring may be formed between Ar1 and Ar2, or between Ar3 and Ar4.
[0058] Furthermore, the number of ring carbon atoms in the aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and more preferably 6 to 12; the number of ring carbon atoms in the condensed aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and more preferably 6 to 12; the number of ring carbon atoms in the aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and more preferably 5 to 12; the number of ring carbon atoms in the condensed aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and more preferably 5 to 12.
[0059] L is a substituted or unsubstituted aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted condensed aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 5 to 50 ring atoms, or a substituted or unsubstituted condensed aromatic heterocyclic group having 5 to 50 ring atoms.
[0060] Furthermore, the number of ring carbon atoms in the aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and more preferably 6 to 12; the number of ring carbon atoms in the condensed aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and more preferably 6 to 12; the number of ring carbon atoms in the aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and more preferably 5 to 12; the number of ring carbon atoms in the condensed aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and more preferably 5 to 12.
[0061] In some specific and preferred embodiments, the aromatic amine compound includes but is not limited to the following compounds HT-1 to HT-62:
[0062]
[0063]
[0064]
[0065]
[0066]
[0067]
[0068] Furthermore, the material of the hole injection layer 101 also includes a p-type dopant material containing a deep LUMO energy level, and the doping concentration of the p-type dopant material is preferably 1 mass % to 10 mass %, and the p-type dopant material is preferably one or more of the above-mentioned compounds HI-1 to HI-18.
[0069] Preferably, the raw materials for preparing the first hole transport layer 102, the second hole transport layer 103, the third hole transport layer 109 and the fourth hole transport layer 110 all include organic hole transport materials, and the organic hole transport material is preferably at least one selected from compounds HT-1 to HT-62.
[0070] It should be noted that the organic hole transport materials in the first hole transport layer 102 , the second hole transport layer 103 , the third hole transport layer 109 and the fourth hole transport layer 110 may be the same substance or different substances.
[0071] Preferably, the main function of the first light-emitting layer 104 is to generate excitons by recombining holes and electrons injected into the light-emitting layer, and the excitons complete the electro-optical conversion process by radiation transition. The film thickness of the first light-emitting layer 104 is not particularly limited, and is preferably 10nm to 100nm.
[0072] Furthermore, the raw materials for preparing the first light-emitting layer 104 and the second light-emitting layer 111 are a combination of the first compound and the second compound, or a combination of the first compound, the second compound and the third compound.
[0073] The first compound is a luminescent material that produces a radiation transition. According to the luminescence mechanism, the first compound can be selected from fluorescent materials, phosphorescent materials, thermally activated delayed fluorescent materials, etc., preferably phosphorescent materials containing coordination metals such as iridium and platinum, thermally activated delayed fluorescent materials containing boron nitrogen derivatives, boron oxygen derivatives, indole and carbazole derivatives, boron fluorine derivatives, and fluorescent materials containing fluoranthene derivatives, pyrene derivatives, and imidazole derivatives. One or more of the following. The second compound is a sensitizer, which acts to provide single and triplet exciton energy for the luminescent material of the first compound, preferably one or more of the thermally activated delayed fluorescent materials containing benzonitrile derivatives, triazine derivatives, pyrimidine derivatives, pyrazine derivatives, imidazole derivatives, benzothiophene oxide derivatives, phenanthroline derivatives, benzonitrile derivatives, and phosphorus oxygen derivatives, or phosphorescent materials containing coordination metals such as iridium and platinum. The third compound is a host material, preferably one or more of carbazole derivatives, triazine derivatives, pyrimidine derivatives, aniline derivatives, benzothiophene derivatives, benzofuran derivatives, and fluorenyl derivatives.
[0074] Preferably, the raw materials for preparing the first electron transport layer 106, the second electron transport layer 105, the fourth electron transport layer 112 and the third electron transport layer 113 all include electron transport materials, and the electron transport materials include aromatic heterocyclic compounds containing one or more heteroatoms, preferably nitrogen-containing ring derivatives, and the nitrogen-containing ring derivatives are selected from one or more of an aromatic ring with a nitrogen-containing six-membered ring skeleton, an aromatic ring with a nitrogen-containing five-membered ring skeleton, a nitrogen-containing six-membered ring condensed aromatic ring compound, and a nitrogen-containing five-membered ring condensed aromatic ring compound.
[0075] Exemplarily, the electron transport materials in the first electron transport layer 106 and the third electron transport layer 113 include but are not limited to the following compounds ET-1 to ET-42. The electron transport materials in the first electron transport layer 106 and the third electron transport layer 113 may be the same substance or different substances.
[0076]
[0077]
[0078]
[0079] Illustratively, the electron transport materials in the second electron transport layer 105 and the fourth electron transport layer 112 include but are not limited to the following compounds EB-1 to EB-12. The electron transport materials in the second electron transport layer 105 and the fourth electron transport layer 112 may be the same substance or different substances.
[0080]
[0081]
[0082] Preferably, an electron injection layer 114 is provided in the second light emitting unit 108 and is in contact with the cathode layer 115, which can promote the injection of electrons from the cathode layer 115 to the electron transport layer. The film thickness of the electron injection layer 114 is not particularly limited, and is preferably 0.5 nm to 10 nm.
[0083] Furthermore, the material of the electron injection layer 114 includes an electron injection material.
[0084] Furthermore, the material of the electron injection layer 114 also includes n-type dopant material or metal.
[0085] Preferably, the main function of the anode layer 100 is to inject holes into the hole transport layer or the light-emitting layer. In order to enable the stacked organic electroluminescent device to obtain higher luminous efficiency and brightness, the light transmittance of the visible area of the anode layer 100 is greater than 80%, and the square resistance is preferably less than 500Ω / cm. The raw material for preparing the anode layer 100 is preferably an anode layer 100 material with a work function of more than 4.5eV. The anode layer 100 material can be listed as indium tin oxide alloy (ITO), tin oxide (NESA), indium gallium zinc oxide (IGZO), silver, etc.
[0086] Furthermore, the anode layer 100 can be formed into an anode layer 100 thin film by thermal evaporation, sputtering, etc., and the film thickness of the anode layer 100 is 10 nm to 200 nm.
[0087] Preferably, the cathode layer 115 mainly functions to inject electrons into the electron injection layer 224, the electron transport layer or the light-emitting layer. The cathode material of the cathode layer 115 is not particularly limited. In order to improve the injection and extraction efficiency of electrons, the material of the cathode layer 115 is preferably a material with a small work function, which may include aluminum, magnesium, silver, magnesium-silver alloy, magnesium-aluminum alloy, aluminum-lithium alloy, etc.
[0088] Furthermore, the cathode layer 115 can be formed into a cathode layer 115 thin film by thermal evaporation, sputtering, etc., and the film thickness of the cathode layer 115 is preferably 10nm to 200nm. In addition, it is understandable that light emission can also be extracted from the cathode side as needed.
[0089] Correspondingly, the present invention also provides an application of the stacked organic electroluminescent device, wherein the stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.
[0090] It should be noted that the present invention has no particular limitation on the sources of the raw materials used in the following examples, and the raw materials may be commercially available products or prepared by methods well known to those skilled in the art.
[0091] The present invention will be further described below with specific embodiments:
[0092] Example 1
[0093] This embodiment provides a stacked organic electroluminescent device, including: an anode layer, a first light-emitting unit, a first connection layer, an interface modification layer, a second connection layer, a second light-emitting unit, and a cathode layer arranged in sequence from bottom to top;
[0094] The first light-emitting unit includes a hole injection layer, a first hole transport layer, a second hole transport layer, a first light-emitting layer, a second electron transport layer and a first electron transport layer arranged in sequence from bottom to top;
[0095] The second light-emitting unit includes a third hole transport layer, a fourth hole transport layer, a second light-emitting layer, a fourth electron transport layer, a third electron transport layer and an electron injection layer which are sequentially stacked from bottom to top.
[0096] Its preparation method is:
[0097] (1) A 30 mm × 30 mm × 0.7 mm glass substrate with an ITO transparent electrode was selected as the anode layer, wherein the thickness of the ITO film was set to 95 nm, and the glass substrate was ultrasonically cleaned in acetone, washing liquid, ultrapure water, and isopropanol for 10 minutes each, wherein the water was changed 3 times during the ultrapure water cleaning, and then the cleaned glass substrate was placed in an oven at 120° C. and baked for 3 hours;
[0098] (2) performing a vacuum plasma cleaning treatment on the baked glass substrate for 10 minutes;
[0099] (3) mounting the above-mentioned glass substrate after the plasma treatment on a substrate frame of a vacuum evaporation device, and firstly co-evaporating the compound HI-7 and the compound HT-10 on the side where the transparent electrode line is formed so as to cover the transparent electrode, wherein the concentration of the compound HI-7 is set to 3 wt %, to form a hole injection layer with a film thickness of 10 nm;
[0100] (4) evaporating compound HT-10 on the hole injection layer to form a first hole transport layer with a thickness of 40 nm;
[0101] (5) evaporating compound HT-48 on the first hole transport layer to form a second hole transport layer with a thickness of 5 nm;
[0102] (6) The third compound combination GH and the first compound GD are co-evaporated on the second hole transport layer to form a first light-emitting layer with a thickness of 40 nm. The concentration of the first compound GD in the first light-emitting layer is set to 5 wt %. The structures of the third compound combination GH and the first compound GD used are as follows:
[0103]
[0104] (7) EB-4 was evaporated on the first light-emitting layer to form a second electron transport layer with a thickness of 10 nm;
[0105] (8) ET-9 was evaporated on the second electron transport layer to form a first electron transport layer with a thickness of 30 nm;
[0106] (9) vapor-depositing an n-type dopant material and an organic electron transport material on the first electron transport layer to form a first connecting layer, wherein the doping concentration of the n-type dopant material decreases from one side of the interface modification layer to the side of the first light-emitting layer; the n-type dopant material, the organic electron transport material, the film thickness, and the doping concentration of the n-type dopant material used are specifically set as shown in Table 1 below;
[0107] (10) vapor-depositing an n-type dopant material and compound N-12 on the first connection layer to form an interface modification layer with a film thickness of 2 nm, wherein the n-type dopant material is ytterbium and the doping concentration is 12 wt %;
[0108] (11) co-evaporating compound HI-7 and compound HT-10 on the interface modification layer to form a second connection layer with a thickness of 10 nm, wherein the concentration of compound HI-7 in the second connection layer is set to 3 wt %;
[0109] (12) evaporating compound HT-10 on the second connecting layer to form a third hole transport layer with a thickness of 50 nm;
[0110] (13) evaporating compound HT-48 on the third hole transport layer to form a fourth hole transport layer with a film thickness of 10 nm;
[0111] (14) The third compound combination GH and the first compound GD were co-evaporated on the fourth hole transport layer to form a second light-emitting layer with a thickness of 40 nm. The concentration of the first compound GD in the second light-emitting layer was set to 5 wt %;
[0112] (15) evaporating EB-4 on the second light-emitting layer to form a fourth electron transport layer with a thickness of 10 nm;
[0113] (16) ET-9 was evaporated on the fourth electron transport layer to form a third electron transport layer with a thickness of 30 nm;
[0114] (17) Liq is evaporated on the third electron transport layer to form an electron injection layer with a thickness of 2 nm. The structure of the Liq used is as follows:
[0115]
[0116] (18) Metal Al was evaporated on the electron injection layer to form a cathode layer with a film thickness of 100 nm.
[0117] Examples 2 to 7 are basically the same as Example 1, except that the first connection layer formed in step (9) has specific related parameters as shown in Table 1 below.
[0118] Table 1 Process parameters for forming the first connection layer in Examples 1 to 7
[0119]
[0120]
[0121] Comparative Example 1
[0122] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 1, except that: no interface modification layer is included, and the doping concentration of the n-type dopant material in the first connecting layer is 1 wt %.
[0123] Comparative Example 2
[0124] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 1, except that:
[0125] The doping concentration of the n-type dopant material in the interface modification layer is 5 wt %.
[0126] Performance Testing
[0127] The stacked organic electroluminescent devices prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were measured using a spectroradiometer CS-2000 (Konica Minolta) and a digital source meter 2420 (Keithley) at 3000 cd / m 2 Driving voltage, external quantum efficiency (EQE), EQE efficiency roll-off and CIE1931 chromaticity coordinates (x, y) at brightness; measured using device lifetime test at a current density of 50 mA / cm 2 When the prepared organic electroluminescent device is driven, the device brightness decays to a lifetime (T95) of 95% of the initial brightness; the performance evaluation results are shown in Table 2 below.
[0128] Table 2 Performance evaluation results of examples and comparative examples
[0129]
[0130]
[0131] From the above results, it can be seen that the doping concentration reduction process of introducing n-type dopant materials in the first connection layer can reduce the driving voltage of the device and improve the life of the device to a certain extent. This is because the decreasing doping process can eliminate the electron injection energy level barrier between the first connection layer and the interface modification layer, so that the carriers generated in the connection layer can be smoothly injected into the light-emitting layer, and avoid the problem of obvious voltage drop at the connection layer. Further, by comparing Example 1 and Comparative Example 1, it can be found that the introduction of the interface modification layer at the first connection layer and the second connection layer can effectively reduce the device driving voltage. This is because the interface modification layer effectively alleviates the energy level mismatch problem between the two connection layers, so that the carriers generated at the connection layer can be injected into the light-emitting unit without a barrier, thereby reducing the voltage drop at the connection layer.
[0132] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A stacked organic electroluminescent device, characterized in that: include: An anode layer, at least two light-emitting units, a cathode layer, and a connection layer for connecting two adjacent light-emitting units are sequentially arranged from bottom to top; the connection layer includes a first connection layer, an interface modification layer, and a second connection layer which are sequentially arranged from bottom to top; The interface modification layer is made of an n-type dopant material and an organic electron transport material, the first connection layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the interface modification layer is greater than the doping concentration of the n-type dopant material of the first connection layer; The doping concentration of the n-type dopant material of the first connection layer gradually decreases from the interface modification layer side to the light-emitting unit side; The second connection layer is composed of a p-type dopant material and an organic hole transport material.
2. The stacked organic electroluminescent device according to claim 1, characterized in that: The doping concentration of the n-type dopant material of the first connection layer decreases in a linear decreasing manner from the interface modification layer side to the light emitting unit side.
3. The stacked organic electroluminescent device according to claim 1, characterized in that: The doping concentration of the n-type dopant material of the first connection layer decreases in a gradient manner from the interface modification layer side to the light-emitting unit side, and the set concentration gradient number is an integer greater than or equal to 3.
4. The stacked organic electroluminescent device according to claim 2, characterized in that: The doping concentration of the n-type dopant material on the side of the first connecting layer close to the interface modification layer is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connecting layer close to the light emitting unit is in the range of 0.5 mass % to 5 mass %.
5. The stacked organic electroluminescent device according to claim 3, characterized in that: The doping concentration of the n-type dopant material on the side of the first connecting layer close to the interface modification layer is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connecting layer close to the light emitting unit is in the range of 0.5 mass % to 5 mass %.
6. The stacked organic electroluminescent device according to any one of claims 1 to 5, characterized in that: The thickness of the first connecting layer is 5nm to 60nm; The thickness of the interface modification layer is 1 nm to 10 nm; The thickness of the second connection layer is 10 nm to 150 nm.
7. The stacked organic electroluminescent device according to claim 1, characterized in that: The n-type dopant material is selected from at least one of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, gold, silver, copper, iron, zinc, platinum, palladium, ruthenium, ytterbium, molybdenum trioxide, vanadium pentoxide, tungsten trioxide, cesium fluoride, cesium carbonate, lithium fluoride, lithium carbonate, 8-hydroxyquinolinate lithium, sodium chloride, and ferric chloride.
8. The stacked organic electroluminescent device according to claim 1, characterized in that: The organic electron transport material is made of nitrogen heterocyclic units, and the nitrogen heterocyclic units are selected from at least one of compounds N-1 to compounds N-58:
9. The stacked organic electroluminescent device according to claim 1, characterized in that: The p-type dopant material of the second connecting layer is a deep LUMO energy level material, and the deep LUMO energy level material is selected from at least one of MoO3, WO3, V2O5, MoO2, Co3O4 and the following compounds HI-1 to HI-18:
10. An application of the stacked organic electroluminescent device according to any one of claims 1 to 9, characterized in that: The stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.
Citation Information
Patent Citations
Series organic light-emitting device
CN114520301A
Laminated organic light-emitting device and application thereof
CN116583133A
Cited By
Laminated organic light-emitting device and application thereof
CN121078902A
Organic light-emitting device and application thereof
CN122373613A